ENDOTHELIAL-TROPIC AND NEPHROPROTECTIVE EFFECTS OF COMBINED ANTIHYPERTENSIVE THERAPY IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - M. E. Statsenko; M. V. Derevyanchenko; M. N. Titarenko; O. R. Pastuchova (Рациональная фармакотерапия в кардиологии)
Aim. To assess the effect of the 24-week antihypertensive therapy with fixed-dose drug combination (lisinopril plus amlodipine) on endothelial dysfunction and renal function in patients with arterial hypertension (HT) and diabetes mellitus (DM) type 2.Material and methods. 30 hypertensive patients with DM type 2 (aged 40-65 years) were included into the study. Endothelial function (plasma and vascular components) and renal function were studied.Results. Combined antihypertensive therapy significantly improved parameters of endothelial function in patients with HT and DM type 2: production of nitric oxide (NO) in blood serum and urine increased by 122.8% and 65.8%, respectively. Along with these secretion of endothelin (ET-1) in serum and urine decreased by 26.1% and by 76.1%, respectively, p<0.05. A statistically significant redistribution of patients by type of microcirculation was established: the share of patients with normal type of microcirculation increased by 73.4%. There was a statistically significant reduction of proteinuria and albuminuria by 58% and 43.6%, respectively. The share of patients with chronic kidney disease with an estimated GFR 30-60 ml/min/1.73 m2 decreased by 16.7%.Conclusions. It has been shown that the prescription of a long-term antihypertensive therapy with dose-fixed combination (lisinopril plus amlodipine) is safe and effective for endothelial function improvement, including renal endothelium, with no negative effect on glucose and lipid metabolism in patients with HT and DM type 2.